Transcatheter mitral valve therapies: A comprehensive review - Bonde, Riya; Kumbasar, Ulaş (Acta Medica, 2024)
Less invasive approaches offer an optimal treatment option for patients with severe mitral regurgitation who is not a candidate for surgical intervention. Favorable outcomes of transcatheter aortic valve replacement have produced great interest in the development of novel minimally invasive transcatheter technologies for repair and replacement of the mitral valve. In this review we aimed to provide an overview of the current transcatheter technologies used to treat mitral regurgitation and help clinicians in selecting the optimal therapy for their patients. We also wanted to provoke clinicians and researchers on how these technologies could be further developed in the future.